UNIT-UNIT PEMROSES PENGOLAHAN LIMBAH CAIR DOMESTIK SKALA RUMAH TANGGA - Rahardjo, Petrus Nugro (Jurnal Teknologi Lingkungan, 2008)
In the last ten years water pollution problem in Jakarta has been becoming more serious. The highly increasing population causes the rising amount of domestic wastewater. Rivers in Jakarta have already been polluted by various wastewaters, such as from industries, domestic and many institutionals (offices, hospitals, markets/shop areas, etc.). It has been well known that the domestic wastewater contributes 70% in causing the river pollution, especially in Jakarta. Therefore it is very important to apply the proper domestic wastewater treatment system which is able to reduce thecontaminants until an environmentally required standard. Some types of domestic wastewater treatment have already been used, but the results do not fulfil the environmental required standard. At least a unit of domestic wastewater treatment should have a control tank as the beginning filter, anaerobic part, aerobic part and a sedimentation tank as the final part of the whole system. An advanced technology using a biofilter media has been proposed and based on the experiment, the result has proven that it can reduce BOD from more than 1,000 ppm to less than 30 ppm. The retention time is about 3 days. The conclusion shows that this new wastewatertreatment system is properly suitable alternative to be applied in domestic area, especially in a densely populated region. By applying the system we can also cope with the water pollution problem caused by domestic wastewater.